Asynchronous Control for Switched T-S Fuzzy Systems Subject to Data Injection Attacks via Adaptive Event-Triggering Schemes - Qi, Yiwen; Yuan, Shuo; Niu, Ben (IEEE transactions on systems, man, and cybernetics. Systems, 2022)
This article addresses the asynchronous event-triggered control problem for switched Takagi-Sugeno (T-S) fuzzy systems under data injection attacks. In reducing communication data update frequency, event-triggered control is an effective control method. The periodic sampling-based adaptive event-triggering schemes with switching structure are first proposed, which can dynamically adjust triggered conditions based on system performance. It is assumed that only the event-triggered and quantized data of the system state and the event-triggered switching signal are available for controllers. However, since the switching signal is sampled and triggered, asynchronous switching may occur between subsystems and subcontrollers. Furthermore, the data injection attacks are considered in the communication network of the system. A time-delay closed-loop switched T-S fuzzy system model is obtained by using a model transformation technique. The resulting criterion provides sufficient conditions to ensure that the closed-loop system subject to data injection attacks is exponential stability with an H_{∞} performance. Moreover, a set of conditions for the co-design of controllers and adaptive event-triggering schemes is presented. Finally, simulations are given to verify the effectiveness of the asynchronous event-triggered control design.